Government failures in the COVID-19 response: A comparative analysis of China, the UK, Italy, and the US - IRATO, Carmela (Journal of Economics Library, 2025)
The COVID-19 pandemic has taken a significant toll on people across the world and leaders have had to tackle unforeseen challenges. From the time the outbreak was first identified in December 2019 to the time of publication, more than 24 million cases of coronavirus had been reported globally, resulting in more than 824,000 deaths. Many countries have taken various measures to combat the virus, but the wildly different responses and response timelines around the world resulted either in failures or successes, leaving people questioning which strategy works best. In this paper, the author examines the accounts of government failure in coronavirus responses in China, the United Kingdom, Italy, and the United States that contributed to the outbreak reaching unprecedented extremes. These government failures are contrasted with Sweden’s successful laissez-faire approach which serves as a crisis response model. In sum, in the attempt to combat the COVID-19 outbreak, governments expanded and squeezed out individual freedoms and liberties which will ultimately have lasting consequences in the post-pandemic world. Keywords. Big government, Government failure, Coronavirus. JEL. F21, F68, O53, K23.